Diversity in the East-Central European Borderlands Memories, Cityscapes, People. - Narvselius, Eleonora (Soviet and post-Soviet politics and society., 2021)
Built on up-to-date field material, this edited volume suggests an anthropological approach to the palimpsest-like milieus of Wrocław, Lviv, Chernivtsi, and Chişinău. In these East-Central European borderline cities, the legacies of Nazism, Marxism-Leninism, and violent ethno-nationalism have been revisited in recent decades in search of profound moral reckoning and in response to the challenges posed by the (post-)transitional period. Present shapes and contents of these urban settings derive from combinations of fragmented material environments, cultural continuities and political ruptures, present-day heritage industries and collective memories about the contentious past, expressive architectural forms and less conspicuous meaning-making activities of human actors. In other words, they evolve from perpetual tensions between choices of the past and the burden of the past. A novel feature of this book is its multi-level approach to the analysis of engagements with the lost diversity in historical urban milieus full of post-war voids and ruptures. In particular, the collected studies test the possibility of combining the theoretical propositions of Memory Studies with broader conceptualizations of borderlands, cosmopolitan sociality, urban mythologies, and hybridity. --